The Challenge Of Implementation Indonesia Industry 4.0 Readiness Index (Indi 4.0) In Infrastructure Company Case Study: At Pt. Hutama Karya (Persero) - Martin Hutagalung; Leo Aldianto (Green Publisher Indonesia, 2024)
This thesis examines the challenges faced by PT Hutama Karya (Persero) in achieving a score of 4.0 on the Indonesia Industry 4.0 Readiness Index (INDI 4.0), highlighting the gap between current industrial practices and the optimal outcomes set by the INDI 4.0 framework. Through qualitative and quantitative research methodologies, this study conducts an in-depth gap analysis across various domains such as management and organization, human resources and culture, products and services, technology, and company operations to evaluate the current state of digital transformation within the company. The findings indicate significant gaps in strategic alignment, technology adoption, and employee engagement with digital initiatives. These gaps contribute to the current INDI 4.0 score of 3.56, limiting the company's progress toward the desired level of industrial readiness. Additionally, survey results show a score of 3.25, indicating that PT Hutama Karya is still in the early stages of implementation with uneven technology adoption. Strategic recommendations are proposed to bridge these gaps, including enhanced strategic coordination, strengthened technology integration, and the development of a digital-supportive culture. These strategies are designed to facilitate a smoother transition to Industry 4.0 for PT Hutama Karya and provide a framework applicable to similar companies in the infrastructure sector. This research contributes to a broader understanding of the digital transformation challenges within the construction and infrastructure industry, offering a detailed roadmap for effective Industry 4.0 implementation